Severe neuropsychiatric symptoms due to vitamin b12 deficiency: a case of pernicious anemia or metformin use? (Sociedade Galega de Medicina Interna, 2015)
Pernicious anemia is the leading cause of vitamin B12 deficiency and requires an early diagnose and proper treatment since it is a reversible form of acute psychosis and demyelinating nervous system disease 1. Less frequently, metformin therapy, especially on high doses and for long time treatment, can also cause vitamin B12 deficit, but the coexistence of anemia and neuropsychiatric symptoms is rarely seen. We describe a case of a 49yearold adult patient with type 2 diabetes medicated with 850 mg of metformin per day, which presented a clinical scenario of severe vitamin B12 deficiency with associated pancytopenia, posterolateral demyelinization of spinal cord and acute psychosis. The investigation was initially negative for pernicious anemia, as upper endoscopy and autoantibodies against intrinsic factor and parietal cells were negative. After excluding other causes, and because serious vitamin B12 deficiency associated with metformin is less frequent in patients with short treatment duration and low daily doses, suspicion of pernicious anemia was maintained. Six months after being discharged, he repeated upper endoscopy with biopsy, which revealed atrophic gastritis and blood autoantibodies became positive. He recovered completely from the neuropsychiatric and hematological dysfunctions with parenteric vitamin B12 treatment. There are several uncommon aspects about this report, namely the severity of the clinical presentation, with serious multiorganic failure. Besides, it is also uncommon that a significant neuropsychiatric impairment coexist with profound bone marrow suppression 2. Also of note is the importance of a great level of suspicion concerning pernicious anemia, since autoantibodies and upper endoscopy can be negative, especially on early phases